“Rerum vel dictu obscenarum” De Subventione Pauperum and the Ambivalence of the Humanitarian Narratives of Early Modernity (2022)
This essay examines the De Subventione Pauperum treatise (On Assistance to the Poor, 1526) by the humanist Juan Luis Vives as a humanitarian narrative of early modernity. Contradictorily, the plan to help the indigent population presents a derogatory view of poverty that reflects the inconsistencies of the civilizing project of Renaissance Christian humanism and reveals the biopolitics of the nascent modern state and humanitarian imperial reasoning. The first section analyzes the treatise as a humanitarian narrative, with a special focus on the role of emotions in the interpellation of the reader, especially the ambivalent presence of the discourse on disgust—an aspect little explored in humanitarianism. The second section examines the plan to regulate public charity and control the indigent population in relation to the new forms of governance of early modernity, based on Foucault’s contributions on the emergence of what was understood at the time as “the police,” a series of technologies of power to regulate the life and work of the population as a whole. The study focuses on the internal contradictions of humanitarian narratives based on the analysis of Vives’ text.